(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article studies the socio-economic ramifications of plastic pollution, including its detrimental effects on industries such as tourism, fisheries, and coastal communities reliant on healthy marine ecosystems for livelihoods. It discusses the disproportionate burden of plastic pollution on developing countries and marginalized communities, exacerbating environmental injustices and inequities. Additionally, the article examines the role of consumer behavior and corporate responsibility in driving solutions to plastic pollution, highlighting the importance of sustainable consumption patterns and corporate initiatives to reduce plastic usage and promote environmental stewardship